2015
DOI: 10.1111/apa.12999
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breastfeeding duration for rural women in a high‐income country: evidence from a cohort study

Abstract: Breastfeeding duration in rural Western Australia is influenced by modifiable factors such as smoking during pregnancy and prepregnancy obesity, therefore strategies to address these risk factors in rural women prior to delivery may contribute to improved breastfeeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…In our study, consistent with previous findings in other cohorts [8][9][10], ABF longer than 4 months was associated with a RTW 2 months later than for no ABF. It is difficult to determine whether women continued ABF because they were given the opportunity not to return to work before 4 months, or whether they chose to return to work later because they wished to breastfeed longer [37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, consistent with previous findings in other cohorts [8][9][10], ABF longer than 4 months was associated with a RTW 2 months later than for no ABF. It is difficult to determine whether women continued ABF because they were given the opportunity not to return to work before 4 months, or whether they chose to return to work later because they wished to breastfeed longer [37].…”
Section: Discussionsupporting
confidence: 93%
“…Among several determinants, increasing attention has been paid to return to work (RTW) as a major constraint to initiate and continue BF [2][3][4]. Numerous previous studies consistently concluded that RTW before 12-16 weeks, compared with later or not at all, was associated with shorter BF duration [5][6][7][8][9][10][11][12][13][14][15]. Indeed, women themselves mentioned RTW as a reason for stopping BF [16][17][18][19][20], though not in all settings [21,22], probably due to cultural norms and work support backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst findings from the RIFS related to factors associated with breastfeeding at discharge from hospital and breastfeeding duration have been reported previously [ 36 , 37 ], this paper provides a more detailed analysis of maternal feeding attitude as an independent influence on breastfeeding behaviour in the rural cohort under study.…”
Section: Methodsmentioning
confidence: 90%
“…18 The Rural Infant Feeding Study (RIFS) aimed to determine the factors associated with breastfeeding practices from birth to 12 months of age in regional and rural Western Australia (WA), the results of which have been reported previously. [19][20][21][22] The aim of this paper was to describe the sources of breastfeeding advice and support and the influence of these sources on breastfeeding practice for women in the first 6 months of their infants' lives.…”
Section: Introductionmentioning
confidence: 99%